THE CONSTRAINTS FACED BY EFL LECTURERS TO THE IMPLEMENTATION OF ONLINE LEARNING - Suryani, Suryani; Meutia, Putri Dini; Fidyati, Fidyati; Prayudiana, Winda; Ugahara, Ugahara (Getsempena English Education Journal, 2024)
The increasing demand for online learning learning has led to its widespread adoption across Indonesia, influencing all levels of education. This sudden shift has pushed educators to quickly adapt to digital technologies, primarily relying on internet-based platforms and email communication. The rapid transition to online learning has created opportunities for pedagogical innovation but also introduced significant challenges, particularly in English language education. This study investigates the obstacles encountered by English as a Foreign Language (EFL) lecturers in implementing online learning. Using a quantitative research approach, data were collected from eight EFL lecturers teaching at both governmental and private universities in Aceh, Indonesia. The data were obtained through online questionnaires, providing insights into the various constraints experienced by these lecturers. The primary challenges reported include a lack of meaningful interaction between lecturers and students, suboptimal learning and evaluation processes, and difficulties in teaching skills-based material online. Other issues highlighted were students' limited understanding of the content, inconsistent internet connection, student disengagement from assignments, lecturer fatigue, and inadequate access to learning resources and support tools. This research provides a comprehensive overview of the barriers faced by EFL lecturers in transitioning to online teaching, offering valuable insights for improving the design and delivery of online education in similar contexts.